Changing frequency of fluctuating light reveals the molecular mechanism for P700 oxidation in plant leaves. (23rd July 2018) - Shimakawa, Ginga; Miyake, Chikahiro
Abstract: Natural sunlight exceeds the demand of photosynthesis such that it can cause plants to produce reactive oxygen species (ROS), which subsequently cause photo‐oxidative damage. Because photosystem I (PSI) is a major source of ROS, plants actively maintain the reaction center chlorophyll of PSI(P700) oxidized under excessive light conditions to alleviate the ROS production. P700 oxidation is universally recognized in photosynthetic organisms as a physiological response to excessive light. However, it is still poorly understood how P700 oxidation is induced in response to fluctuating light with a variety of frequencies. Here, we investigated the relationships of photosynthetic parameters with P700 oxidation in Arabidopsis thaliana under a sine fluctuating light with different frequencies. As the photon flux density of the light increased, P700 was oxidized concurrently with the chlorophyll fluorescence parameter qL unless the electron acceptor side of PSI was limited. Conversely, we did not observe a proportional relationship of non‐photochemical quenching with P700 oxidation. The mutant crr‐2, which lacks chloroplast NADPH dehydrogenase, was impaired in P700 oxidation during light fluctuation at high, but not low frequency, unlike the pgrl1 mutant deficient in PGR5 and PGRL1 proteins, which could not oxidize P700 during light fluctuation at both high and low frequencies. Taken together, our findings suggested that the changing frequency of fluctuating light reveals the tracking performance of molecular mechanisms underlying P700 oxidation.